THE RELATIONSHIP BETWEEN VITAMIN D AND BONE METABOLISM MARKERS AND THEIR EFFECTS ON THE REPRODUCTIVE SYSTEM IN WOMEN WITH HYPERPROLACTINEMIA - Baltabaeva G.Sh., Muminova Z.A. (Central Asian Journal of Medicine, 2025)
This article examines the status of vitamin D and bone metabolism markers (osteocalcin, P1NP, CTX) in reproductive-aged women diagnosed with hyperprolactinemia (HPRL). Clinical observations were used to assess the impact of these changes on ovulation, endometrial receptivity, and the probability of pregnancy. Based on a statistical analysis involving 90 patients, it was found that vitamin D levels significantly decreased in women with HPRL, accompanied by suppressed bone formation markers and elevated bone resorption indicators. A negative correlation was established between PRL and 25(OH)D (r = –0.56), and between PRL and osteocalcin (r = –0.48). Women with low 25(OH)D levels showed reduced bone mineral density (T-score of –2.1 in the femur, –2.3 in the spine), impaired ovulatory function, and diminished endometrial receptivity. In Group III (HPRL + vitamin D deficiency), osteopenia was found in 67% of cases. Significant prolongation of the menstrual cycle (41.2 ± 7.5 days), reduced estradiol levels (72.1 ± 15.7 pg/ml), and increased CTX (0.83 ± 0.15 ng/ml) demonstrate the complex negative influence of HPRL and vitamin D deficiency. Based on these findings, assessing vitamin D status and bone turnover markers in HPRL patients offers an opportunity to improve reproductive health.